Interesting Organization of Mathematics Lessons - Noriyeva Aziza Jasur qizi (Zien Journals, 2023)
The article presents the possibilities of using specialized software such as Mathcad, Matlab, Mapl, Matematica in learning algebraic materials, and these possibilities serve to organize lessons effectively and interestingly.
Keywords: Mathcad; Matlab; Mapl; Matematica